Patient-reported assessment of medical care for chronic inflammatory skin diseases: an enterprise-based survey - Wolk, Kerstin; Schielein, Maximilian; Maul, Julia-Tatjana; Widmayer, Fontaine; Wanke, Kerstin; Fischmann, Wolfgang; Nathan, Petra; Sabat, Robert (Frontiers in Medicine, 2024)
Background Chronic inflammatory skin diseases (CISDs) are among the most common diseases in the Western world. Current estimates of medical care for CISDs are primarily based on surveys among patients in medical care facilities and on health insurance data. Aim Survey-based examination to what extent CISD patients in health-aware environment consider their skin disease to be controlled. Methods The survey of CISD patients was carried out in 2022 among the employees of a pharmaceutical company located in Germany and Switzerland. Software-based, anonymous, self-reported questionnaires were used. Results The number of employees, who answered the questionnaire, was 905. Of these, 222 participants (24.5%) reported having at least one CISD. 28.7% of participants with CISD described their disease as being hardly or not controlled. Regarding the nature of disease, more than one third of participants suffering from hidradenitis suppurativa (HS) or psoriasis fell into the hardly/not controlled category. In contrast, the largest proportion of participants with chronic spontaneous urticaria (43%) or atopic dermatitis (42%) considered their CISD to be completely or well controlled. Only 35.5% of CISD sufferers stated that they were currently under medical care for their skin condition. Being under medical care, however, had no influence on the extent CISD sufferers considered their skin disease to be controlled. The number of active CISD episodes but not the total number of symptomatic days per year was negatively associated with poor disease control (p = 0.042 and p = 0.856, respectively). Poor disease control had a negative effect on the personal and professional lives of those affected, as deduced from its positive association with the extent of daily activity impairment and presenteeism (p = 0.005 and p = 0.005, respectively). Moreover, 41.4 and 20.7% of participants with hardly/not controlled disease stated that their CISD had a moderate and severe or very severe impact on their overall lives (p < 0.001), respectively. A severe or very severe impact of their CISD on their overall life was most commonly reported by participants with HS. Conclusion Medical care for CISDs, even in an environment with high socio-economic standard and high health-awareness, still appears to be limited and has a negative impact on individuals and society.